Recent progress on fabrication of zinc oxide nanorod-based field effect transistor biosensors - Siti Shafura A Karim,; Chang, Fu Dee; Burhanuddin Yeop Majlis,; Mohd Ambri Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Zinc oxide is a unique n-type semiconducting material, owing to wide bandgap of ~3.37 eV, non-toxic, bio-safe and biocompatible with high isoelectric point of ~9.5, make it as promising biomaterial to be utilized as sensing matrix in biosensor applications. In addition, ZnO that possess high electron affinity provide a good conduction pathway for the electrons hence result in significant electrical signal change upon detection to target biomolecules. Moreover, high surface area of ZnO nanorod enhance immobilization of enzymes, hence, increase the device performance. Field effect transistor (FET)-based biosensor offer simplicity in handling and label-free, has also become research topic among researchers for novel biosensor development. This review aims to explore the preparation of ZnO nanorod using hydrothermal method and investigate the fabrication of ZnO nanorod-based FET biosensor. Thus, contribute to enhance understanding towards biosensor development for health monitoring, especially based on FETs structure devices.